The People’s Review protocol: planning an innovative study powered by the public - Quinn, Éle; Dawson, Shoba; Holt, Jeremy; Hossain, Shahed; Logullo, Patricia; O’Brien, Ann; Smith, Maureen; Stewart, Derek; Treweek, Shaun; Young, Charlene; Noone, Chris; Moher, David; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Systematic reviews provide the best quality evidence about the effectiveness of health treatments. However, systematic reviews and the important role they play in healthcare are not well understood beyond the walls of academia and healthcare. Systematic reviews can help the public make more informed health choices, based on the best available evidence. The People’s Review aims to provide an opportunity to members of the public to plan and complete a full systematic review online in a supportive and engaging manner. It will be a learning-by-doing experience to support the public’s understanding of what reviews are, how they are done, why they matter, and how they can be used to support everyday health decisions. Methods In The People’s Review the public will conduct a full systematic review, deciding the review question, planning the review, working on the parts of the review, and deciding how to share the review findings, in a ‘learning by doing’ process. The review will be conducted online in eight stages using Cochrane Crowd, an existing citizen science platform. The team working behind-the-scenes of The People’s Review will design, produce, and share learning material to support the public’s understanding at each stage of the review. Discussion Involving the public in a systematic review online will enable members of the public to understand and use systematic reviews in everyday health choices. It provides the public with a unique ‘learning by doing’ opportunity to get to grips with what systematic reviews are and how they are produced. This article describes how we plan to involve the public in The People’s Review. It is not a protocol for the systematic review itself – this will be published separately once the project has commenced, and the public have decided the review question.

Plain English summary It can be difficult to make health decisions today. We are exposed to a huge amount of information available 24/7 on a smartphone. It is easy to find all sorts of news, figures, and advice about healthcare. However, not everything is reliable. Our decisions should be based on the best evidence available — but how do we find it? A systematic review is a method used by researchers, clinicians, and others to find all the evidence that has been published about a healthcare treatment. Systematic reviews use clear and careful steps to find relevant studies, assess the trustworthiness of the studies, and put together the results of those studies. These steps give us the best evidence available about whether a healthcare treatment works or not. However, the methods of systematic reviews can be complex and hard to understand. The People’s Review is an innovative project that will give the public the opportunity to learn about systematic reviews by doing a systematic review. Anyone can take part and help us do a systematic review together. People will learn about what systematic reviews are, how they work and why they matter. We will support the public throughout, so that everyone will learn new skills. In the end, we will have a systematic review led and conducted by the public. This article describes how we plan to involve the public in all the key stages of The People’s Review through an easy-to-use online platform. Our plans were also formulated and decided with members of the public on the planning group.